Factor VII Mie: Homozygous Asymptomatic Type I Deficiency Caused by an Amino Acid Substitution of His (CAC) for Arg(247) (CGC) in the Catalytic Domain - Ohiwa, Michiaki; Hayashi, Tatsuya; Wada, Hideo; Minamikawa, Kouzou; Shirakawa, Shigeru; Suzuki, Koji (Thrombosis and Haemostasis, 1994)
We found hereditary factor VII deficiency in a clinically asymptomatic family, and characterized their factor VII gene and the abnormal molecule using recombinant DNA techniques. The propositus was a 45-year-old woman who was noted to have a prolonged prothrombin time. The level of factor VII antigen of the patient was 25.9% of that of normal individuals and the level of factor VII activity was 28% and 24%, when tested using rabbit brain tissue factor and human placental tissue factor in a one-stage clotting assay, respectively. Two of her sisters had almost the same reduced levels of factor VII antigen and activity, and her parents who are first cousins, a son, a daughter and a niece had moderately reduced leves of both factor VII activity and antigen. To identify the mutation site, all the coding exons and exon-intron boundaries of the factor VII gene of the propositus were amplified using the polymerase chain reaction (PCR), then subcloned and sequenced. One mis- sense mutation (G to A) was identified in exon VIII of the gene resulting in an amino acid substitution of His(CAC) for Arg(247)(CGC) in the gene product. PCR using a mutagenic primer to introduce a new kpaL I site into the mutant allele of the patient’s factor VII gene revealed that this allele was inherited in the affected individuals in the pedigree. Transient expression assays using BHK cells transfected with an expression vector containing the mutant factor VII cDNA suggested that this mutation leads to factor VII deficiency by impairing secretion of the mutated factor VII. This is the first report of a single point mutation which induces factor VII deficiency with both activity and antigen reduced in parallel.